Windswept the story of wind and weather - De Villiers, Marq (Walker Distributed to the trade by Holtzbrinck Publishers, 2006)
lthough sometimes destructive, wind is one of the elements that make life possible. Wind warms the higher latitudes and moderates the equatorial regions, and carries evaporated moisture from the oceans to the land. Even hurricanes are an essential part of the planet's self-regulatory system. This book is the story of humankind's long struggle to understand wind and weather, from the wind gods of ancient times to early discoveries of the dynamics of air movement to high-tech schemes to control hurricanes. Author de Villiers explains the science of wind and presents personal stories of people's encounters with gales and storms, including his own. Although we have made great strides in understanding how wind affects weather, there is much left to learn about how global warming and pollution may impact wind. The stakes are high because, clearly, anything that affects the winds eventually affects human life.--From publisher description.